2016
DOI: 10.1080/15564886.2016.1250691
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Offender Versatility and Specialization Across a 23-Year Span for At-Risk Young Men

Abstract: This study examined patterns and correlates of offender specialization versus versatility, or more random offenses, among 206 at-risk men. Both official records and self-report data of offending from late childhood to ages 31/32 were used. Aggregate-level and individual-level analyses indicated that the predominant offender pattern for this sample was versatility. Three correlates of offender versatility were examined (offense frequency, early onset, gang association). Aggregate-level findings consistently rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
1
4
0
10
Order By: Relevance
“…In general, life-course research has shown that most offenders are generalists, who are quite versatile in the different kinds of crime they commit throughout their life (e.g., [10,29,35,38,39,65]). On the other hand, short-term specialization also exists (e.g., [29,35]).…”
Section: Offending Over the Life-coursementioning
confidence: 99%
See 1 more Smart Citation
“…In general, life-course research has shown that most offenders are generalists, who are quite versatile in the different kinds of crime they commit throughout their life (e.g., [10,29,35,38,39,65]). On the other hand, short-term specialization also exists (e.g., [29,35]).…”
Section: Offending Over the Life-coursementioning
confidence: 99%
“…For example, employment may reduce opportunities for most types of offending, but it could at the same time increase opportunities for fraud or other white-collar or employment-enabled crimes [39], which may drive an offender to specialize in these types of crime. The life-course specialization literature generally focuses on the question to what extent and when offenders show specialization over their life-course (e.g., [10,29,35,39,65]) and how this should be measured [13,35].…”
Section: Offending Over the Life-coursementioning
confidence: 99%
“…Durante los últimos años la investigación sobre la violencia que se genera en el interior del núcleo familiar ha ocupado una posición cada vez más importante en la agenda de investigación en criminología, política y salud pública; aun así, la evidencia obtenida a través de resultados de investigaciones longitudinales sigue siendo escasa, requiriéndose continuar con este tipo de trabajos (Akers y Kaukinen, 2009;DeLisi et al, 2019;Hulme et al, 2019;Richards et al, 2013;Verbruggen et al, 2019;Weatherburn y Rahman, 2018;Wiesner et al, 2018). Aunque existe evidencia que indica que muchos agresores de violencia intrafamiliar delinquen una única vez, respondiendo posiblemente a la efectividad disuasoria del sistema penal, en la mayoría de los casos eso no se cumple (Buzawa y Hirschel, 2008).…”
Section: Abstract: Intimate Partner Violence Domestic Violence Criminunclassified
“…La medida en que los delincuentes se especializan en tipos específicos de delito (por ejemplo, delitos violentos) tiene implicaciones importantes para la teoría y las políticas públicas (DeLisi et al, 2019;Wiesner et al, 2018); así, al diferenciar entre especialistas y versátiles se pueden identificar las estrategias de intervención más eficaces, ya sea para aplicar correctamente teorías generales del comportamiento antisocial sobre aquellos que participan indistintamente en todo tipo de delito, o bien teorías especiales de violencia social y familiar sobre los agresores que se especializan en ese tipo de violencia (Lishak et al, 2019), aun cuando las estrategias especializadas en violencia doméstica también han demostrado que producen beneficios indirectos en en cuanto a otras formas de delincuencia, aunque con costos más elevados (Weatherburn y Rahman, 2018).…”
Section: Article In Pressunclassified
See 1 more Smart Citation